Study of Sidewalk Autonomous Delivery Robots and Their Potential Impacts on Freight Efficiency and Travel - Jennings, Dylan; Figliozzi, Miguel (Transportation research record, 2019)
E-Commerce and package deliveries are growing at a fast pace and there is an increased demand for same-day deliveries. Established delivery companies and new startups are investing in technologies that reduce delivery times or increase delivery drivers’ productivity. In this context, the adoption of sidewalk automated (or autonomous) delivery robots (SADRs) has a growing appeal. SADRs are pedestrian sized robots that deliver items to customers without the intervention of a delivery person. Because SADRs travel on sidewalks they have been the subject of increasing regulation by local agencies in the U.S. The three research questions that guide this research effort are: (a) What are the limitations imposed by existing regulations in the U.S.?, (b) What are the technical capabilities of existing SADRs?, and (c) Given the existing capabilities and regulations, what are the time/cost savings and efficiencies that SADRs can bring about? The first part of the research discusses current U.S. regulations on SADRs and reviews existing SADR devices and their capabilities. Building on this knowledge, the second half of the research presents a novel model to estimate delivery time and number of customers served utilizing a combination of SADRs and a special delivery van. These results are compared with a baseline (or prevailing) delivery system utilizing only a conventional delivery van and human driver. Results, insights, and potential implications are discussed. The results show that SADRs can provide substantial cost and time savings in some scenarios. Furthermore, the introduction of SADRs may significantly reduce on-road travel per package delivered.